2007
DOI: 10.1104/pp.106.089904
|View full text |Cite
|
Sign up to set email alerts
|

The GCR1, GPA1, PRN1, NF-Y Signal Chain Mediates Both Blue Light and Abscisic Acid Responses in Arabidopsis

Abstract: Different classes of biotic (e.g. plant hormones) and abiotic (e.g. different wavelengths of light) signals act through specific signal transduction mechanisms to coordinate higher plant development. While a great deal of progress has been made, full signal transduction chains have not yet been described for most blue light-or abscisic acid-mediated events. Based on data derived from T-DNA insertion mutants and yeast (Saccharomyces cerevisiae) two-hybrid and coprecipitation assays, we report a signal transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
165
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(182 citation statements)
references
References 69 publications
9
165
2
3
Order By: Relevance
“…In contrast, ectopic expression of LEC1 and LEC2 induces somatic embryo formation on the cotyledons and leaves of arabidopsis seedlings (Lotan et al., 1998; Stone et al., 2001). Later it was found that L1L/NUCLEAR FACTOR Y subunit B6 (NF‐YB6) and three other NF‐Y subunits, A1, 5 and 9, with roles in embryo development, drought resistance, and ABA perception (Kwong et al., 2003; Li et al., 2008; Warpeha et al., 2007), also induce spontaneous SE in seedlings when overexpressed (Mu, Tan, Hong, Liang, & Zuo, 2013). The remaining two LAFL genes, FUS3 and ABI3 , do not induce SE when overexpressed, but do confer cotyledon identity to leaves (Gazzarrini, Tsuchiya, Lumba, Okamoto, & McCourt, 2004; Parcy et al., 1994).…”
Section: A Network Of Arabidopsis Transcription Factors Controls Somamentioning
confidence: 99%
“…In contrast, ectopic expression of LEC1 and LEC2 induces somatic embryo formation on the cotyledons and leaves of arabidopsis seedlings (Lotan et al., 1998; Stone et al., 2001). Later it was found that L1L/NUCLEAR FACTOR Y subunit B6 (NF‐YB6) and three other NF‐Y subunits, A1, 5 and 9, with roles in embryo development, drought resistance, and ABA perception (Kwong et al., 2003; Li et al., 2008; Warpeha et al., 2007), also induce spontaneous SE in seedlings when overexpressed (Mu, Tan, Hong, Liang, & Zuo, 2013). The remaining two LAFL genes, FUS3 and ABI3 , do not induce SE when overexpressed, but do confer cotyledon identity to leaves (Gazzarrini, Tsuchiya, Lumba, Okamoto, & McCourt, 2004; Parcy et al., 1994).…”
Section: A Network Of Arabidopsis Transcription Factors Controls Somamentioning
confidence: 99%
“…In plants, heterotrimeric G proteins composed of Ga-, Gb-, and Gg-subunits function as important signaling agents mediating responses to a range of biotic and abiotic signals (Assmann, 2005;Temple and Jones, 2007;Warpeha et al, 2007;Okamoto et al, 2009;Nilson and Assmann, 2010). In animal cells, it has been shown that UV-B activates the Ga-Gbg complex to release free Ga and Gbg, both of which result in HB-EGF secretion and subsequent activation of the EGF signal transduction pathway (Seo et al, 2004(Seo et al, , 2007Seo and Juhnn, 2010), suggesting that both Ga and Gbg are functional units to transmit UV-B signaling.…”
Section: Ga Plays An Important Role In Uv-b Guard Cell Signalingmentioning
confidence: 99%
“…In contrast to mammalian cells, where multiple a, b, and g genes exist, there is only one prototypical Ga (GPA1), one Gb (AGB1), and two known Gg (AGG1 and AGG2) genes in Arabidopsis (Arabidopsis thaliana; Temple and Jones, 2007). Despite the comparative simplicity of players, G proteins have been shown to participate in multiple signaling pathways in Arabidopsis, including developmental processes, phytohormone responses, and responses to biotic and abiotic environmental signals such as pathogens, ozone, drought, and light (Assmann, 2005;Temple and Jones, 2007;Warpeha et al, 2007;Okamoto et al, 2009;Nilson and Assmann, 2010).…”
mentioning
confidence: 99%
“…Phytochrome-mediated stabilization of Fed-1 mRNA requires active translation, the 59 UTR, and active photosynthetic electron transport (Chiba and Green, 2009). Light-mediated increases in transcript stability have also been reported for small subunit of Rubisco (RbcS) transcripts in petunia (Petunia hybrida; Sathish et al, 2007) and the light-harvesting chlorophyll-binding (Lhcb) transcripts in pea (Warpeha et al, 2007).…”
mentioning
confidence: 99%